Effect of Streptozotocin-induced Diabetes on Clock Gene Expression in Tissues Inside and Outside the Blood-brain Barrier in Rat - Šoltésová, D.; Monošíková, J.; Koyšová, L.; Veselá, A.; Mravec, B.; Herichová, I. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The circadian system allows organisms to remain synchronized with rhythmic environmental changes with a 24-h period. The molecular mechanism of circadian oscillations is based on the rhythmic expression of clock genes organized in feedback loops. Alterations in the circadian system contribute to the development of several pathological conditions including diabetes, but the exact mechanisms responsible for such alterations are not known. Therefore, we employed streptozotocin-induced diabetes to elucidate the influence of metabolic changes on clock gene (clock, npas2, per2) expression in peripheral oscillators in tissues inside (frontal cortex, cerebellum) and outside (heart, kidney) the blood–brain barrier. Diabetes was induced by streptozotocin injection. Seventeen days later, sampling was performed during a 24-h cycle. Gene expression was measured using real-time PCR. We observed a phase advance in rhythmic clock gene expression in the heart and kidney of diabetic rats. The study also focused on the possible role of npas2 in locomotor activity regulation in diabetic animals. The most pronounced changes were observed in the frontal cortex, which displayed up-regulation of npas2 expression. A change in locomotor activity was observed in diabetic rats during the dark phase of the 24-h cycle. We suggest that the altered function of the frontal cortex induced by diabetes might contribute to the modified behavior of diabetic rats.
Keywords: frontal cortex; heart; cerebellum; per2; npas2; locomotor activity